Does psychological well-being mediate economic well-being? short-term evidence from a multifaceted program in the Philippines. Issue 3 (3rd July 2021) - Bloem, Jeffrey R.; Gandhe, Rashmita
ABSTRACT: Can changes in psychological well-being lead to changes in economic well-being? Across many settings, the view that inexpensive psychological interventions can lead to meaningful change in economic well-being has become popular. Examining data from participants of a multifaceted program in the Philippines we find that program participants experience (i) positive changes in income and expenditures, (ii) relatively large changes in measures of psychological well-being, but that (iii) these changes in psychological well-being do not mediate changes in economic well-being. This suggests, at least in the short-term, that changes in psychological attributes may have small effects on measures of economic well-being.